Evaluation of the right ventricular function in hypertrophic obstructive cardiomyopathy: a strain and tissue Doppler study - Zemánek, David; Tomašov, Pavol; Linhartová, Kateřina; Veselka, Josef; Přichystalová, P (Physiological research, 2010)
We investigated the utility of strain, strain rate, and tissue Doppler imaging (TDI) for the evaluation of the right ventricle (RV) impairment in patients with a hypertrophic obstructive cardiomyopathy (HOCM) who underwent a successful alcohol septal ablation (ASA) and were without RV hypertrophy. A group of 19 patients suffering from HOCM with 22 controls was compared. The parameters of TDI were evaluated in mitral and tricuspid annulus. Strain and strain rate derived from TDI were assessed in an apical free wall of RV, as well as in basal segments of the left ventricle. Between both groups, there were significant differences only in isovolumic pre-ejection time (79.2±17.3 ms vs. 58.5±8.1 ms, p<0.01), isovolumic relaxation time (104.7±26.2 ms vs. 77.3±24.5 ms, p<0.01), myocardial performance (Tei) index measured from TDI (0.61±0.14 vs. 0.49±0.09, p<0.01), and early peak diastolic velocity of TDI (10.6±1.67 cm/s vs. 12.6±2.21 cm/s; p<0.05). Our results suggest the impairment of both systolic and diastolic RV function in patients suffering from HOCM. TDI-related parameters appear to be more sensitive than strain and strain rate for evaluation.
Keywords: Aged; tepový objem; lidé; lidé středního věku; senioři; ženské pohlaví; Ventricular Function, Right; diastola; financování organizované; Female; mužské pohlaví; Cardiomyopathy, Hypertrophic; hypertrofická kardiomyopatie; Mitral Valve; Financing, Organized; mitrální chlopeň; Middle Aged; Systole; systola; dopplerovská echokardiografie; Humans; Diastole; funkce pravé komory srdeční; Male; Echocardiography, Doppler; Stroke Volume